Immune responses against the hepatitis C virus and the outcome of therapy - Klenerman, P; Barnes, E (Springer New York, 2008)
The hepatitis C virus (HCV) sets up persistence in the majority of those infected. In doing so, it evades both innate and adaptive immune responses. However, in a reasonable fraction of patients (20-50%), there is long-term control of viremia through some effective combination of host responses. It is generally considered that cellular immune responses-mediated by CD4+ and CD8+ T cells-play a major role in determining this successful outcome, although they do so in concert with many other cellular and humoral mediators (Ward et al., 2002). © 2008 Springer Science+Business Media, LLC.